Fructo-oligosaccharide effects on serum cholesterol levels. An overview - Costa,Graciana Teixeira (2015)
PURPOSE:To address the effects of fructooligosaccharides (FOS) intake on serum cholesterol levels.METHODS: We performed a search for scientific articles in MEDLINE database from 1987 to 2014, using the following English keywords: fructooligosaccharides; fructooligosaccharides and cholesterol. A total of 493 articles were found. After careful selection and exclusion of duplicate articles 34 references were selected. Revised texts were divided into two topics: "FOS Metabolism" and "FOS effects on plasma cholesterol."RESULTS: The use of a FOS diet prevented some lipid disorders and lowered fatty acid synthase activity in the liver in insulin-resistant rats. There was also reduction in weight and total cholesterol in beagle dogs on a calorie-restricted diet enriched with short-chain FOS. Another study found that 2g FOS daily consumption increased significantly serum HDL cholesterol levels but did not ensure a significant reduction in levels of total cholesterol and triglycerides.. Patients with mild hypercholesterolemia receiving short-chain FOS 10.6g daily presented no statistically significant reduction in serum cholesterol levels. However, when FOS was offered to patients that changed their lifestyle, the reduction of LDL cholesterol and steatosis was higher.CONCLUSIONS: Fructooligosaccharides intake may have a beneficial effect on lipid metabolism and regulation of serum cholesterol levels in individuals that change their lifestyle. FOS supplementation use in diets may therefore be a strategy for lowering cholesterol.